Bush at War - Bob Woodward 1943- (USA Simon & Schuster, 2003)
In this book, the author tells the behind-the-scenes story of how President George W. Bush and his top national security advisers, after the initial shock of the September 11 attacks, led the nation to war. Extensive quotations from the secret deliberations of the National Security Council - and firsthand revelations of the private thoughts, concerns and fears of the president and his war cabinet - make [the book a] chronicle of a modern presidency in time of grave crisis. Based on interviews with more than a hundred sources and four hours of exclusive interviews with the president, [it] reveals Bush's sweeping, almost grandiose, vision for remaking the world. [It] includes a ... portrait of CIA director George Tenet, ready and eager for covert action against terrorists in Afghanistan and worldwide. It [also] follows a CIA paramilitary team leader on a covert mission inside Afghanistan to pay off assets and buy friends with millions in U.S. currency carried in giant suitcases
"With an update on the war with Iraq"--Cover
Keywords: History, Geography and Archaeology (3GdJGQjN hGdLZQGajG hGdBKGQs; War on Terrorism, 2001-2009; September 11 Terrorist Attacks, 2001; National security -- United States -- Decision making; General